Malaysian capital market: sukuk versus conventional bond / Noriza Mohd Saad and Nor Edi Azhar Mohamad - Mohd Saad, Noriza; Mohamad, Nor Edi Azhar (2012)
This study investigates and estimates the impact of bond facets to issuer performance using multivariate regression model which is applied into three categories: (i) firm’s profitability which is proxies by return on asset (ROA), return on equity (ROE), net profit margin (NPM) and operating profit margin (OPM); (ii) firm’s efficiency is proxy by asset turnover (AT) and (iii) firm’s capital structure is proxy by debt to equity in Malaysia. On the other hand, we applied ANOVA approach to compare between sukuk or Islamic bonds and conventional bonds. Secondary data was used for issuance (N= 563) cover the 2005-2009 periods which are gathered from Bank Negara Info Bond Hub website and Rating Agency Malaysia (RAM) for such a bond facets. However, data on issuer performance has been obtained from Bloomberg software and Thompson Data Stream. The results revealed that there is a statistically significant relationship among variables and most of the public listed issuer was issued sukuk as compared to conventional bonds. Based on the regression result it was recommended that bond issuer should deeply considered bond rating in their future issuances to tap the bond market at competitive rate since it was statistically significant to all regressions model.